2000
DOI: 10.1016/s0008-6363(99)00382-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased apoptosis in the heart of genetic hypertension, associated with increased fibroblasts

Abstract: Apoptosis occurs in the cardiomyocytes of genetic hypertension although fibroblasts are increased, and a significant, age-dependent increase in apoptosis is observed. The increase in apoptosis occurs before the difference in blood pressure is detectable. The ACE inhibitor ramipril may be useful for prevention of apoptosis in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 10 publications
5
36
2
Order By: Relevance
“…Interestingly, an increased cell death occurs before ABP increase in the SHR heart, as reported by Liu et al 17 Additional studies using cardiac cell cultures, as we found specific type I TRH receptor expression in cultured neonatal cardiomyocytes and fibroblasts (unpublished results), would be necessary to elucidate the mechanism by which TRH induces the development of LVH. Figure 5.…”
Section: Perspectivessupporting
confidence: 73%
“…Interestingly, an increased cell death occurs before ABP increase in the SHR heart, as reported by Liu et al 17 Additional studies using cardiac cell cultures, as we found specific type I TRH receptor expression in cultured neonatal cardiomyocytes and fibroblasts (unpublished results), would be necessary to elucidate the mechanism by which TRH induces the development of LVH. Figure 5.…”
Section: Perspectivessupporting
confidence: 73%
“…In addition, we found the number of apoptotic nuclei/mm 2 in the TG to be more than that of the SD in both the SA and the AV nodes in all age-groups (two-day, one-week and two-week). The results correspond to the work of Liu et al,15 who demonstrated that there is increased apoptosis in the heart of spontaneously hypertensive rats (SHR).…”
Section: Discussionsupporting
confidence: 91%
“…Z-VAD-FMK, a pancaspase inhibitor (36)(37)(38)(39)(40)(41)(42), can inhibit cell death in response to mechanical injury. Interestingly, our results showed that Z-VAD-FMK could inhibit chondrocyte death more effectively in chondroitinase ABC-treated explants than in control explants.…”
Section: Discussionmentioning
confidence: 99%